Does Serum R-Spondin-1 Play a Role in PCOS Pathophysiology? - Oğuzhan Sıtkı Dizdar; Derya Koçer; Yasin Şimşek; Osman Başpınar; Hatice Kayış Topaloğlu (Genel Tıp Dergisi, 2022)
Objective: Many new inflammatory and metabolic markers are considered to be involved in etiology of Polycystic ovary syndrome (PCOS). R-spondin-1 (Rspo1) is a member of the roof plate-specific spondin protein family. Rspo1 levels have been associated with obesity and insulin resistance. We aimed to investigate whether Rspo1 has a role in the pathophysiology of PCOS.